A review of real-world data on the effects of aripiprazole on weight and metabolic outcomes in adults. (August 2014) - Citrome, Leslie; Kalsekar, Iftekhar; Baker, Ross A.; Hebden, Tony
Abstract Background: Metabolic abnormalities observed with atypical antipsychotic treatment may be specific to each antipsychotic medication. The association between atypical antipsychotics and risk factors for cardiovascular disease prompted the American Diabetes Association (ADA) and the American Psychiatric Association (APA) to issue a consensus statement that categorized aripiprazole and ziprasidone as atypical antipsychotics with a lower likelihood of metabolic abnormalities. Objective: The aim of the current systematic review was to evaluate real-world studies (i.e. observational/naturalistic and open-label studies) assessing the risk for weight gain, dyslipidemia, glucose abnormalities, and diabetes mellitus in adult patients receiving treatment with atypical antipsychotics, with a specific focus on aripiprazole. Methods: A systematic PubMed search for articles published between 1 January 2000 and 4 October 2011 was performed using the following search terms in the title and abstract: aripiprazole, atypical, glucose, insulin, cholesterol, triglycerides, diabetes, hemoglobin A1c, weight, body mass index, and hyperlipidemia. Results: Twenty-two peer-reviewed articles were found that assessed the metabolic effects associated with aripiprazole treatment, including studies from small observational trials to large databases (n = 15 to n > 1, 700, 000). Thirteen articles reported observational or naturalistic studies, and nine were open-label trials evaluating weight gain, dyslipidemia, glucose abnormalities, and the risk of developing diabetes in adult patients receiving treatment with aripiprazole. Compared with other atypical antipsychotics, aripiprazole was either less likely to have an impact or had a comparable impact on weight gain and dyslipidemia; the degree of effect appeared to be dependent on study design. In addition, there was less risk of diabetes mellitus with aripiprazole compared with most other atypical antipsychotic agents. Conclusions: Consistent with data from randomized controlled studies, the current review of observational/naturalistic and open-label studies suggests aripiprazole may be associated with a lower risk than other commonly used atypical antipsychotics for metabolic adverse events in adults, consistent with the ADA/APA consensus statement.